OS ATOS DE 8 DE JANEIRO NA NARRATIVA DE UMA MÍDIA CONSERVADORA: CONTRIBUIÇÕES DA PSICOLOGIA SOCIAL - Douglas Edio Maurer Teixeira (2025)
TThe event of January 8, 2023, marked by the invasion of the Praça dos Três Poderes in Brasília by supporters of former president Jair Bolsonaro, represents a significant moment in Brazilian politics. During this protest, public buildings were vandalized, including the Palácio do Planalto, the Supreme Federal Court, and the National Congress. The invaders called for the seizure of power and the removal of the government elected in 2022, claiming fraud in the elections. Based on Bardin's Content Analysis, this study aims to investigate the narratives surrounding the events of January 8 in a journalistic medium, represented in this case by the online news site Jovem Pan. Using key descriptors, 768 articles were selected, from which a corpus of 472 articles was established after applying exclusion criteria. Following the reading of the articles, the data pertaining to them were analyzed and categorized. The results revealed that the studied media outlet, in its messages about the events, conveys a narrative that reflects its values and ideological positions. The final considerations highlight the limitations arising from the scarcity of sources on a recent event, with academic production still in its infancy, and suggest that further studies could be conducted based on this one, focusing on investigations that analyze the verbalizations, reactions, and speeches of the participants recorded in videos or other media regarding January 8. Keywords: Media, January 8th, Jovem Pan, Social Psychology.